Prospective teachers' opinions about concept cartoons integrated with modular instructional design [Modüler ögretim tasarimiyla entegre edilmiş kavram karikatürleri hakkinda öǧretmen adaylarinin görüşleri] - (:unkn) unknown (My University, 2011)
The purpose of this research study is to determine prospective teachers' opinions about concept cartoons integrated with modular instruction design. The research was conducted by using a descriptive method. The study group of the research included 4th grade students at (n=44) Marmara University Faculty of Technical Education Textile Education Department, taking a guidance course. The course was conducted by using the concept cartoons embedded in the modular instruction design. In the study, a survey form was used in order to obtain the prospective teachers opinions about modular instruction design and concept cartoons used in design. The concept cartoons used in modular instruction design are positive and that concept cartoons affect learning positively and increase motivation.
Keywords: Concept cartoons; Modular instruction design